CONSEQUENCE OF COVID-19 PANDEMIC ON SHARE PRICE MOVEMENTS IN CAPITAL MARKET - Iswi Hariyani; Rhama Wisnu Wardhana (UNEJ e-Proceeding, 2022)
The capital market longing as funding for companies and other institutions (e.g. the government) and for investing activities. The capital market provides a source of spending with a longer-term, which is invested in capital goods to create and multiply the means of production, creating markets and promoting healthy economic activity. The COVID-19 pandemic since March 2020 and its policies, such as the lockdown, have triggered a multidimensional global crisis in various fields, especially in the economic sector. Indonesia composite index or "IHSG" can be used to indicate the movement of the Indonesian stock market and stock-based investments, such as stock mutual funds. This research is included in normative juridical research. The authors use 2 (two) approaches, the statutory and conceptual approaches. There are 3 (three) problem formulations: first, Whether the Covid-19 pandemic has affected stock price movements in the capital market. Second, How the Covid-19 pandemic has affected stock price movements in the capital market. Third, How is the government's policy to anticipate the impact of the Covid-19 pandemic on the movement of capital market stock prices. The authors find that the implications of covid-19 are reflected in decline in stock values but also increasing the digital transformation. From the government's perspective,with OJK, several stimulus policies have been issued that are able to maintain market stability and the "IHSG".Keywords: Investment, Capital Market, Covid-19.